Ultrasonographic comparison of bilateral patellar tendon dimensions in patients treated via intramedullary tibial nailing using a transpatellar approach - Samet Erinç; İrfan Esenkaya; Oğuz Şükrü Poyanlı; Burak Özturan; Muzaffer Ayaz; Afşar Timuçin Öztürk (Acta Orthopaedica et Traumatologica Turcica, 2018)
Objective: One of the most common complications following intramedullary nailing of a tibial shaft fracture is anterior knee pain. The etiology of pain remains unclear. Patellar tendon entry point is the most suspected reason for anterior knee pain. This study, sonographically examined the patellar tendons of patients treated via intramedullary nailing. Methods: Thirty-two patients with a tibial shaft fracture requiring intramedullary nailing via a transpatellar approach were included in the study. After all patients were grouped by reference to the presence of anterior knee pain, bilateral patellar tendon ultrasonography was performed. Results: Thirty-two patients were included in the study. Patients were measured postop average in 38.3 months (10th months - 84th months). It was determined that 10 patients of total 32 (31.3%) had anterior knee pain. There were no statistically differences between study groups in the length of patellar tendon. In the painless group; patellar tendon was wider and thicker in the operated side than the non operated side. The mean differences in the thickness between operated side versus non – operated side of the painless group were 5.3 ± 1.8 in the operated side and 3.9 ± 1.4 in the non – operated side (p = 0.007 < 0.05). The corresponding values for width of the patellar tendon was 29.6 ± 3.3 in the operated side and 27.6 ± 3.8 in the non – operated side (p = 0.007 ˂ 0.05). As a result, there were no statistically significant differences between width and thickness of the patellar tendons in the painful group, on the contrary, in the painless group; patellar tendons were wider and thicker in the operated side than those in the non - operated side. Mean values for thickness of the operated and non-operated side were 5.9 ± 2.3 and 4.2 ± 2.0, respectively (p = 0.059 > 0.05). Mean values for width of the operated and non-operated side were 30.2 ± 4.5 and 28.5 ± 4.0, respectively (p = 0.103 > 0,05). Conclusion: Based on the ultrasonographic investigation of their patellar tendons after intramedullary nailing of a tibial shaft fracture, in the painless patients group; the patellar tendon was wider and thicker in the operated side than the non – operated side, however, in the painful patients there were no statistically significant differences between this parameters. Although the number of patients was not sufficient to conclude precise relation between patellar tendon entry point and anterior knee pain, we determined that thicker and wider tendon might be less related to anterior knee pain. Level of evidence: Level IV, therapeutic study. Keywords: Tibia fracture, Intramedullary nailing, Ultrasound, Anterior knee pain, Transpatellar approach, Patellar tendon